Heaven's fury : a novel - Frey, Stephen W. (Atria Books, 2010)
Preparing for a dangerous snowstorm in rural Wisconsin, sheriff Paul Summers finds his efforts hampered by the arrival of a mysterious group of criminals, a suspicious disappearance, rumors of cult activity, and the murder of a former lover.